HALODOC APPLICATION USABILITY: A COMBINED SUS AND SEQ - Chara Aulia Urrohim; Andreas Rio Adriyanto (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research evaluates the usability of the Halodoc application for new users through an Interaction Design-based study. Quantitative methods, specifically the System Usability Scale (SUS) and the Single Ease Question (SEQ), were employed, supplemented by qualitative observation and interviews to diagnose User Interface (UI) and User Experience (UX) problems. Quantitative results revealed significant usability issues, demonstrated by an average SEQ score of 3.2 on a 1-7 scale. The average SUS score was 52.0, which categorizes the platform as "Poor" and in the "Marginal" zone of acceptability, indicating users likely face discomfort and difficulty. These findings were reinforced by qualitative data, which pointed to design constraints such as a cluttered interface, confusing menus/icons, and critical functionality problems with the nearest location feature. The study concludes that user interaction with the Halodoc platform is currently unsatisfactory and requires substantial improvements, particularly in interface design, to resolve identified usability violations and achieve a satisfactory user experience.